Firearm injury prevention counseling for patients with traumatic brain injury: a survey of brain injury physicians - Ramsay, Ian; Miranda-Cantellops, Natalia Del Mar; Acosta, Oliver; Shapiro, Lauren T. (Frontiers in Neurology, 2023)
Background Survivors of traumatic brain injury are at increased risk for firearm-related injuries, including suicide. Aims To determine current practices of Brain Injury Medicine (BIM) physicians and their rehabilitation teams in assessing patients’ access to firearms and in providing firearm safety education, and the impact of having received training on this topic on physicians’ likelihood of inquiring about patients’ access to firearms. Methods 14-item web-based cross-sectional survey of 86 U.S. physiatrists board-certified in BIM. Results 81% of respondents indicated they believe BIM physicians should counsel their patients on firearm safety but only 12.9% reported always doing so. Fifteen percent reported always inquiring about their patients’ access to firearms. 88.2% indicated having never received formal training on firearm injury prevention counseling. Physicians who received such training had 7.5 times higher odds of reporting at least sometimes inquiring about patients’ access to firearms than those who were not trained [95% confidence interval (1.94, 28.64)]. They also had 5.7 times higher odds for reporting being at least moderately comfortable providing patients firearm safety counseling [95% CI: (1.39, 23.22)]. Conclusion While most BIM specialists who responded to this survey believe they should counsel patients on firearm safety, few always or usually do so. Moreover, most do not routinely inquire about their patients’ access to firearms. The provision of firearm injury prevention training to BIM physicians was strongly associated with an increased likelihood they will inquire about their patients’ access to guns and with an improved comfort level in providing counseling on this subject matter.